2020
DOI: 10.3389/fimmu.2020.00274
|View full text |Cite
|
Sign up to set email alerts
|

IDO Targeting in Sarcoma: Biological and Clinical Implications

Abstract: Sarcomas are heterogeneous malignant mesenchymal neoplasms with limited sensitivity to immunotherapy. We recently demonstrated an increase in Kynurenine Pathway (KP) activity in the plasma of sarcoma patients treated with pembrolizumab. While the KP has already been described to favor immune escape through the degradation of L-Tryptophan and production of metabolites including L-Kynurenine, Indoleamine 2,3 dioxygenase (IDO1), a first rate-limiting enzyme of the KP, still represents an attractive therapeutic ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 27 publications
2
33
0
Order By: Relevance
“…More recently, a study of 203 sarcoma specimens identified PD-L1 expression on malignant and immune cells in 23% of all cases [40], consistent with another large sarcoma cohort study [11]. Reports from IHC studies suggest high heterogeneity between histologic subtypes [41].…”
Section: Pd-l1supporting
confidence: 66%
See 2 more Smart Citations
“…More recently, a study of 203 sarcoma specimens identified PD-L1 expression on malignant and immune cells in 23% of all cases [40], consistent with another large sarcoma cohort study [11]. Reports from IHC studies suggest high heterogeneity between histologic subtypes [41].…”
Section: Pd-l1supporting
confidence: 66%
“…In pleomorphic dermal sarcoma, all cases identified as having high CD8 infiltration had LAG-3+ immune cells [39]. Similarly, high CD8+ TILs correlated positively with IDO-1 staining in soft-tissue sarcomas [40]. Furthermore, pretreatment specimens from a phase 2 clinical trial showed that two pleomorphic sarcoma subtypes, leiomyosarcoma and UPS, had around 70% cases with IDO-1 expression, while only 29% of other softtissue sarcomas met the same criteria for IDO-1 [52].…”
Section: Others: Ido Lag3 Tim3mentioning
confidence: 90%
See 1 more Smart Citation
“…In a study on the role of IDO1 in sarcomas, its expression was highlighted in 39.1% of STSs, and in 65.3% if we consider the subgroup with high levels of CD8 + TILs. Furthermore, the IDO1/KP signaling pathway contributes to an immunosuppressive phenotype of STSs and is involved in primary resistance to PD1 inhibitors [ 42 ].…”
Section: Molecular Markers Associated With Prognosismentioning
confidence: 99%
“… 89 IDO1 inhibition by navoximod has been shown to decrease plasmatic Kyn/Trp ratios and tumor Kyn levels. 90 In sarcoma-bearing mice, navoximod used alone or combined with a PD-L1 blocker could neither efficiently control tumor growth nor affect the tumor immune cell infiltrate. 90 However, in the 4T1 murine breast tumor model, navoximod synergizes with doxorubicin 91 - 93 to elicit an antitumoral immune response and to control tumor growth.…”
Section: Preclinical Advancesmentioning
confidence: 99%